2016
DOI: 10.1088/0964-1726/25/12/125005
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on the mitigation of end-stop impacts in a magnetorheological damper operated by the mixed mode

Abstract: This paper presents mitigation behaviour of magnetorheological (MR) damper operated with a mixed working modes. A combination of the shear and squeeze modes is employed in the structure of MR damper to obtain the field-dependent normal yield stress as well as strengthen the squeeze effect. The experimental evaluation shows that when the piston is squeezing the bottom gap from the stroke of 25 to 26 mm, the sudden increase of squeeze force is observed confirming the existence of the mitigation effect. It is als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…This is due to their unique property that depicts fast real-time responses toward different intensities of magnetic fields [1]. Among these MR materials, MRF has established itself in applications especially related to the hydraulic devices in the automotive sector, such as torque and force transmitting devices [2], dampers [3,4], clutches [5], and brakes [6]. On the other hand, for the past few years, MRE has attracted an increasing interest as it is able to exhibit a desirable performance owing to the stability of magnetizable particles in a solid-based matrix [7].…”
Section: Introductionmentioning
confidence: 99%
“…This is due to their unique property that depicts fast real-time responses toward different intensities of magnetic fields [1]. Among these MR materials, MRF has established itself in applications especially related to the hydraulic devices in the automotive sector, such as torque and force transmitting devices [2], dampers [3,4], clutches [5], and brakes [6]. On the other hand, for the past few years, MRE has attracted an increasing interest as it is able to exhibit a desirable performance owing to the stability of magnetizable particles in a solid-based matrix [7].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the investigations on normal stress behavior of MRG are relatively infrequent. However, normal stress of MR material has a strong effect on the performance of some engineering devices, such as MR damper (Yazid et al, 2016) and MR finishing (Lambropoulos et al, 2010). Moreover, the normal stress behavior is also significant for understanding the mechanism of the MR effect and the evolution of particle microstructures.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an alternative arrangement, squeeze mode, in which the fluid is subjected to compressive and tensile stresses, has been identified for small motion isolation [17,18]. In addition, it has been recently reported that the efficacy of MR fluid devices could be enhanced under a mixed-mode operation [19,20]. The comparative performance of MR fluid devices using theoretical and experimental procedures has been extensively reported in the technical literature [15,21,22].…”
Section: Introductionmentioning
confidence: 99%